HGG-06. EARLY GABAERGIC NEURONAL LINEAGE DEFINES DEPENDENCIES IN HISTONE H3 G34R/V GLIOMA. (1st June 2021) - Liu, Ilon; Bjerke, Lynn; Cruzeiro, Gustavo Alencastro Veiga; Rogers, Rebecca F; Grabovska, Yura; Panditharatna, Eshini; Mackay, Alan; Barron, Tara; Shaw, McKenzie; Hoffman, Samantha E; Hack, Olivia A; Quezada, Michael A; et al.
Abstract: High-grade gliomas harboring H3 G34R/V mutations exclusively occur in the cerebral hemispheres of adolescents and young adults, suggesting a distinct neurodevelopmental origin. Combining multimodal bulk and single-cell genomics with unbiased genome-scale CRISPR/Cas9 approaches, we here describe a GABAergic interneuron progenitor lineage as the most likely context from which these H3 G34R/V mutations drive gliomagenesis, conferring unique and tumor-selective gene targets essential for glioma cell survival, as validated genetically and pharmacologically. Phenotypically, we demonstrate that while H3 G34R/V glioma cells harbor the neurotransmitter GABA, they are developmentally stalled, and do not induce the neuronal hyperexcitability described in other glioma subtypes. These findings offer a striking counter-example to the prevailing view of glioma origins in glial precursor cells, resulting in distinct cellular, microenvironmental, and therapeutic consequences.